2012
DOI: 10.1111/j.1440-1843.2011.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of non‐invasive ventilation for the relief of dyspnoea in exacerbations of chronic obstructive pulmonary disease; a systematic review

Abstract: Limited data exist to determine if NIV relieves subjective dyspnoea in AECOPD. Due to limitations in these studies, it is not possible to definitively conclude if NIV relieves dyspnoea. Standardized reporting and analysis of patient reported outcomes will facilitate objective comparisons of interventions with respect to symptom relief. Future studies involving NIV should routinely incorporate patient reported outcomes in order to answer the important clinical question: 'Does NIV relieve dyspnoea?'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
1
20
0
2
Order By: Relevance
“…In another study, comparing QoL between patients with advanced COPD and patients with cancer, patients with COPD reported higher levels of physical discomfort with uncontrolled shortness of breath in 78% 280. A recent review of the 4 RCTs that have explored whether NIV relieves dyspnoea in AECOPD concluded that benefit was likely but that study limitations constrained a confident conclusion 281. With regard to physical symptoms, breathlessness and fatigue are dominant in AECOPD.…”
Section: Care Planning and Delivery Of Carementioning
confidence: 99%
“…In another study, comparing QoL between patients with advanced COPD and patients with cancer, patients with COPD reported higher levels of physical discomfort with uncontrolled shortness of breath in 78% 280. A recent review of the 4 RCTs that have explored whether NIV relieves dyspnoea in AECOPD concluded that benefit was likely but that study limitations constrained a confident conclusion 281. With regard to physical symptoms, breathlessness and fatigue are dominant in AECOPD.…”
Section: Care Planning and Delivery Of Carementioning
confidence: 99%
“…ECOG PS was highly correlated with physical function (Smith et al, 2012) and is the main correlate of not working (Phipps et al, 2011;Gomes et al, 2012;Pantilat et al, 2012). Poor ECOG PS of a patient would become a greater stressor for the caregiver (Tordoff et al, 2012) and family caregivers of terminal cancer patients who had poor ECOG PS scores were likely to need more assistance with patients dependent on care for activities of daily living or IADL including help with transportation, shopping, homemaking, emotional support, nutritional care, nursing care, and personal care (Baker et al, 2011;Chochinov et al, 2011;Cohen et al, 2012;Fairfield et al, 2012;Gomes et al, 2012;Pantilat et al, 2012;Tordoff et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Patients in our study reported that NIV often alleviated their breathlessness. A recent systematic review found that the quality of data from randomised clinical trials of NIV did not allow a conclusion as to whether NIV relieved dyspnoea 27. This discrepancy in findings attests to the utility of qualitative studies in capturing lived experience beyond the quantitative symptom assessment measures and speaks to the need for ongoing work in this area.…”
Section: Discussionmentioning
confidence: 99%